Phenotypic characterization and mitocondrial DNA analysis of marcapomacocha llamas, Perú - Cano Z, Lady (2012)
The k’ara llama population of Marcapomacocha district, Yauli province, department of Junín, Peru is known for the preponderance of ancestral coloration in the herds. In order to document the apparently unique characteristics of these animals, phenotypic and DNA analyses were carried out on 50 llamas (5 male and 45 female aged 1 to >4 years) from the region. The coat coloration pattern of the animals was uniform, with tones varying from yellow brown to dark red brown, similar to that of the ancestral Peruvian guanaco (Lama guanicoe cacsilensis), while the chest, abdomen and inner surface of the legs are white with a grey-black head and white outlining of the lips, eyes and ears. Biometric analysis of 30 adults (4 years of age and greater) yielded the following results: withers height 123.2 ± 12.2 cm; rump height 119.5 ± 8.5 cm; chest width 36.5 ± 2.7 cm; chest girth 136.4 ± 5.5 cm; ear length 19.6 ± 2.7, upper and lower neck circumferences 42.8 ± 2.7 and 63.9 ± 4.7 cm respectively. Body length averaged 118.5 ± 5.3 cm and body weight was 152.5 ± 12.3 kg. Based on a survey of the literature, the Marcapomacocha llamas are taller, longer and heavier than k´ara llamas from other regions of Peru. Analysis of a diagnostic segment of the cytochrome b gene revealed that all 50 llamas had the ancestral guanaco haplotype, possibly indicating that no hybridization with alpacas has occurred.